Efecto de la aplicación de bio-formulados de PGPRs (rizobacterias promotoras del crecimiento vegetal) en la germinación y el desarrollo de Ochroma Pyramidale (Cav. ex Lam.) Urb. (balsa) y Gmelina arbórea Roxb. (melina) en vivero - Valdez López , Mayi Anahís (2023)
The use of Plant Growth Promoting Rhizobacteria (PGPRs) reduces the use of chemical fertilizers that damage the microbiota of the region's soils, which are overloaded with anthropogenic compounds. The objective of the present work was to determine the effect of the application of bioformulated PGPRs on the germination and development of balsa and melina at nursery level. For the study of the different variables, a Completely Randomized Design (CRD) was implemented with five treatments; T1: CHA0, T2: R4, T3: 2/12, T4: 3/8 and T5: Control; consisting of three replicates, subjected to Tukey's test at 95% probability. The bio-formulated M3 Roc-Raq (BIOQPGPRs) was used at 20% in which the seeds were soaked and inoculated in the seedlings every 15 days for 45 days (20 ml per seedling).